A young man with changes affecting 20 nails - Santos, Vitorino Modesto; Azevedo, Micheline Silva Abreu; Brito, Kátia Rejane Marques; Luz, Larissa Almondes; Ribeiro, Kayursula Dantas (Revista de Medicina e Saúde de Brasília, 2015)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]-->The nail involvement in pemphigus vulgaris has been associated with the severity of disease; and paronychia, onychomadesis, Beau’s lines and nail hemorrhages, are more often reported. In the young patient herein described the conspicuous nail changes developed during the convalescent period of disease, after a long-term administration of azathioprine and sulfone. Nail changes can be reversible and these drugs are safe and useful to the pemphigus control. Case reports might contribute to better knowledge about phenomena not well understood yet.<!--[if gte mso 10]> <![endif]-->